Developing the Leader-Member Exchange Theory in Nursing: Seeing from an Introvert Eye - Barbara, Laksita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Objective: This paper aims to find a gap in the current findings and provide a recommendation by exploring the Leader-Member Exchange (LMX) theory with regards of introversion Methods: A literature review is conducted to analyse the current findings of the development and application of LMX theory.Results: The LMX theory focuses on the interaction that happens in leadership and reveals the role of relationship in affecting the organisation outcomes. The LMX theory has been developed in four stages to meet the needs of the application at various organisational levels. In the nursing profession, the application of LMX theory shows positive outcomes in affective commitment, job satisfaction, and reduced intention to leave. However, the studies of this theory in nursing has hardly provided the solution to overcome the limitations of out-group members. The studies show the discrimination that is caused by the different treatment of the leader to each member. The other issue is subjectivity. The high-quality interaction is more likely to be formed by people with sociable traits compared to those with solitaire personality. One of the personality types which might have a less likeliness to be the in-group member is introverted personality.Conclusion: The LMX theory has given a pivotal awareness in nursing profession regarding the different relationship developed by a supervisor with each nurse. However, there is hardly prescriptive approach to escalating the exchange quality to the higher level. Thus, this paper emphasises the need to enhance justice climate and identify as well as be aware of the leader’s and member’s characteristics.